Cytogenetic characterization of Caesalpinia spinosafrom Tarma and Palca (Junín) - López, Alberto (2013)
Somatic chromosomes of Caesalpinia spinosa (Feuillée ex Molina) Kuntze, “Tara”, wild populations of Huinco and Palca (Junín) regions were studied. The specie were diploid (2n=24). Chromosomes were small. The karyotypes showed the same chromosome number, they found differences in morphological parameters of the same, with the karyotype formula for the town of Huinco: 6m + 6 sm and the town of Palca: 5m + 7 sm.